Compartmentalization of an ABC triblock copolymer single-chain nanoparticle via coordination-driven orthogonal self-assembly. Issue 24 (12th June 2017) - Cui, Zhigang; Cao, Hui; Ding, Yi; Gao, Pan; Lu, Xinhua; Cai, Yuanli
Abstract : We present coordination-driven intramolecular orthogonal self-assembly of ABC triblock copolymer into protein-like compartmentalized SCNP, whose sub-10 nm ultrafine subdomains are discrete and can respond to aqueous surroundings individually. Abstract : Herein, we present supramolecular compartmentalization of an ABC triblock copolymer single-chain nanoparticle (SCNP) using coordination-driven orthogonal intramolecular self-assembly in aqueous solution. A well-defined ABC-type triblock copolymer was synthesized via visible-light-mediated RAFT aqueous sequential block copolymerization. It possesses protonated imidazolium-motifs in the A-, NH3 + -motifs in C-, and hydroxyl-motifs in B-block. Coordination-driven orthogonal self-assembly locally occurring upon deprotonation (A-block within pH 3.3–4.4 and C-block within pH 5.3–6.4) has been evidenced by UV-vis spectroscopy, 1 H NMR, dynamic light scattering (DLS), NMR diffusion-ordered spectroscopy (DOSY), and atomic force microscopy (AFM). A blank regime of pH 4.4–5.3 guarantees locally orthogonal intramolecular self-assembly without mutual interference. Dialysis and pH-cycling results illustrate that the inherent different subdomains are discrete and can individually respond to an external stimulus, with potential biomimetic functions in terms of sub-10 nm ultrafine internal heterogeneity.